Dose-dependent effects of ultrasound therapy on hepatocellular carcinoma - Sultan, Laith R (IEEE Int Ultrason Symp, 2020)
Non-invasive ischemic cancer therapy requires reduced blood flow whereas drug delivery and radiation therapy require increased tumor perfusion for a better response. In this study we investigate the hypothesis that different dose models of antivascular ultrasound therapy (AVUS) can have opposite effects on hepatocellular carcinoma (HCC) tumor blood flow. HCC was induced in 22 Wistar rats by ingestion of diethylnitrosamine (DEN) for 12 weeks. Rats received AVUS treatment at low and high doses. Low dose group received 1 watt/cm(2) ultrasound for 1 min with 0.2 mL microbubbles injected IV. High dose group received 2 watts/cm(2) for 2 min with 0.7 mL microbubbles IV. A sham group did not receive any treatment. Tumor perfusion was measured before and after AVUS with contrast-enhanced ultrasound. Quantitative perfusion measures: perfusion index (PI) and peak enhancement (PE) were obtained from each AVUS dose. After high-dose AVUS, PE and PI decreased by an average of 58.1 ± 4.9% and 49.1 ± 6.5 % respectively. Conversely, following low dose AVUS, PE and PI increased from baseline by an average of 47.8 ± 4.5% % and 20.3 ± 2.4 %, respectively. The high-dose AVUS therapy decreased tumoral perfusion, an effect that could be used for noninvasive ischemic therapy. Conversely, low-dose therapy increased tumor perfusion, which may improve drug delivery or radiation therapy. These opposite therapy effects can support multiple roles for AVUS in cancer therapy by tunable modulation of blood flow in tumors.